HISTORY OF PR IN CANADA an annotated bibliography and critical historiography of public relations.. research in canada. - Braun, Sandra L. (ROUTLEDGE, 2024)
A first of its kind, this annotated bibliography provides an overview of the development of public relations research in the Canadian context. A valuable resource for researchers, students or practitioners, this bibliography surveys the landscape of public relations research in Canada. It orientates readers to this unique history, identifies gaps in research, suggests topics of future research, and offers critical historiography. This reference work will be of interest to scholars, students and practitioners in the fields of strategic communications, marketing or communications, providing a greater understanding of communications research in various Canadian contexts such as government, industry, corporate and nonprofit.
Keywords: Public relations -- Canada -- History.; elektronické knihy; electronic books